Boundaries on Turkish export-oriented industrialization - Deniz Güvercin (Journal of Economic Structures, 2020)
This study examines the Turkish experience of export-oriented industrialization by emphasizing its linkage to previous capital accumulation model and developments and by the evolution of political and economic institutions. The study emphasizes that the structural drawbacks in Turkish economy that emerged in the economic development process aggravated in post-1980 period and aims to uncover the political and economic mechanisms leading to its aggravation. The VAR methodology is used to model Turkish economy's experience of export-oriented industrialization by using the data for the period 2007: Q1-2017: Q4. The impulse response analysis results show that export is responsive to investment and capacity utilization and responsive to interest rate and import in the negative direction. Import is responsive to export, investment and capacity utilization in a positive direction and decreases with interest rate. Investment increases with export, but decreases with imports. Additionally, the debt level increases with export and investment, but decreases with import and import increases the interest rate and export decreases the interest rate.
Keywords: F14; F34; F43; 330; Export-oriented industrialization; Import substitution industrialization; Structural drawbacks; Public sphere; VAR